Correlation between components of tolerance caregivers in Jahrom hospitals using factor analysis - Golestan Jahromi, Fatemeh; Keramati, Akram; Sarokhani, Mandana; Sayehmiri, Kourosh; Zamani, Narges; Peyman, Hadi; sheikhan, Zohreh (Advances in Nursing & Midwifery, 2013)
Abstract Background and aim: Nurses have an important role in caring of clients. So, determine the component of burden, identifying structure of components and correlation between them can effective in determine the new component and identifying the effective factors of burden. The aim of current study is to determine the correlations between CBI components among nurses in Jahrom hospitols by using factor analysis. Materials and methods: In this research, 158 of nurses in Jahrom hospitals with stratified sampling enrolled to study. by using car-giver burden ills questionnaire, five burden’s components that involve "Time dependence burden", " Developmental burden", "Physical burden", " Social burden" and "Emotional burden" were assessed. Data were analyzed by Pierson correlation coefficient, regression models and factor analysis. Results: Time dependence burden, Developmental burden, Physical burden, Social burden and Emotional burden of women were significantly higher than men (p<0.05). There was a significant difference between workplace and different burden components (p<0.05). Time dependence burden of CCU nurses and triage nurses were in a high and low level, respectively. There was a significant correlation between Emotional burden and Social burden (P=0.000). Factor analysis showed that nurse’s burden contains two main factors, that these two factors predicting 64% of total data variance. According to factor analysis physical burdens and Developmental burden and Physical burden were an independent factor, social burden and emotional burdens were another independent factor. Conclusion: There was a significant difference between gender and workplace with components of Burden. Women’s Burden in caring of patients was more than men which can related to physical and emotional characteristics of women. Key words: Time dependence burden, Developmental burden, Physical burden, Social burden, Emotional burden, Factor Analysis